Worldview Under Stress: Preliminary Findings on Cardiovascular and Cortisol Stress Responses Predicted by Secularity, Religiosity, Spirituality, and Existential Search - Schnell, Tatjana; Fuchs, Dietmar; Hefti, René (Journal of religion and health, 2020)
This study reports preliminary findings on the hypothesis that worldview can predict cardiovascular and cortisol responses to social stress. Based on theory and previous findings, we assumed that worldview security would provide a basis for stress resilience. Accordingly, religious and atheist individuals were expected to show higher stress resilience than spiritual and agnostic participants. Likewise, dimensional measures of religiosity and atheism were hypothesized to predict decreased, and existential search—indicating worldview insecurity—was hypothesized to predict increased physiological stress responses. Subjects included 50 university students who completed online questionnaires and took part in a standardized social stress test (Trier Social Stress Test). Systolic and diastolic blood pressure (SBP/DBP), heart rate (HR), and salivary cortisol (SC) were assessed at baseline, immediately after stress testing, and during a forty-minute recovery period. Worldview comparisons revealed lower cardiovascular stress responses among religious than among atheist and spiritual participants and particularly high baseline SC among spiritual participants. Across the entire sample, existential search showed substantial positive correlations with SBP, HR, and SC stress parameters. The findings suggest that worldview security might partly explain the health benefits often associated with religion.